Fitoextracción de Pb y Cr de relaves mineros de la poza Santa Catalina del distrito de quiruvilca, santiago de chuco usando la especie brassica juncea (mostaza) - Esquivel Carbajal, Betty Natali (2019)
In this research work, the bioaccumulation capacity of lead and chromium from mining tailings was evaluated using the species Brassica juncea (mustard). It was distributed in four treatments T1, T2, T3 and T4 and a control, to which an organic substrate was added in percentages of 100%, 75%, 50% and 25% of tailings plus the substrate and attachments, all were performed in based on 1 kg and with four replicates per treatment, having as exposure time of 40 days with two harvests fulfilled 20 and 40 days respectively. The growth parameters were analyzed and the number of leaves was counted every three days, on each harvest date the dry weight of the plant organs and the root length were taken. For the analysis of heavy metals in the plants the Mass Spectrometer with Inductively Coupled Plasma of the School of Environmental Engineering was used. The results indicate that the treatments with higher tailings concentration prevent a good development of the plant and biomass production due to the scarce availability of organic matter and nutrients, the growth rates at 40 days was 0% in T1, 17.4% in T2, 63.9% in T3, 109.2% in T4 and the control plant grew 154.5%. As for the bioaccumulation of heavy metals, the root part concentrated a greater amount of Pb and the leaves accumulated a greater amount Cr, the T3 treatment being with the best phytoextraction conditions of 8 mg / kg MS in the root and 23. 35 mg / Kg MS of Cr in the leaves. Taking into account the ability to accumulate metals from Brassica juncea, the results suggest that with the organic substrate used it could be a favorable solution for its growth and improvement in the phytoextraction of contaminated soils, improving its cumulative capacity